The Role of the ELAVL Family of RNA-Binding Proteins in LRRK2-Dependent Models of Parkinson's Disease - Negeri, Olanta (Université d'Ottawa / University of Ottawa, 2024)
Parkinson's disease (PD) is the second most common neurodegenerative disease, yet it has no cure. It is characterized by the loss of dopaminergic neurons and accumulation of dense aggregates, primarily composed of α-synuclein protein. Many causative genes have been identified including SNCA, encoding α-synuclein, and Leucine-rich-repeat kinase 2 (LRRK2). The LRRK2 G2019S mutation is known to cause hyperactive kinase activity, but its cellular functions, including its kinase substrates, remain poorly understood. PD has many risk factors including environmental and genetic modifiers. Polymorphisms in the Embryonic lethal-abnormal vision-like 4 (ELAVL4) gene modify PD age-of-onset or susceptibility. Incidentally, a genetic screen in Drosophila identified an ELAVL homologue as required for LRRK2-induced pathology. Therefore, we hypothesized that LRRK2 phosphorylates ELAVL4 to control phenotypes relevant to PD. We discovered that three neuronal ELAVLs including ELAVL4 (also known as HuD) bind to, and post-transcriptionally regulate mRNA encoding α-synuclein and LRRK2. We also show that LRRK2 phosphorylates HuD and its homologues HuB and HuC. This controls binding of nELAVLs (i.e., HuB, HuC, and HuD) to mRNA and post-transcriptionally regulates mRNA abundance and splicing in the mouse midbrain. In mice, the complex interaction between HuD and Lrrk2 G2019S is associated with motor deficits, dopaminergic neuron loss, and accumulated α-synuclein protein levels. Targets of nELAVLs are also selectively misregulated in iPSC-derived neurons and tissues from PD patients. In a model of PD-relevant inflammation, we also show that the ubiquitously expressed ELAVL homologue, HuR, controls LRRK2 protein levels. We show that mice lacking Lrrk2 are more susceptible to an acute model of dextran sodium sulfate (DSS) chemical-induced colitis. Lrrk2-deficient mice treated with DSS also show accumulated α-synuclein in brain tissue. Using in vitro models and mouse tissue we show that LRRK2 controls HuR binding to RNA probes and to the proinflammatory cytokine Tnfa in colon tissue, and this has implications for intestinal pathology relevant to PD. Together, this suggests that misregulation of ELAVLs may be implicated in neurodegeneration and inflammation observed in Parkinson's disease.
Keywords: Parkinson's disease; LRRK2; ELAVL/Hu; post-transcriptional regulation